Theories and cures of the rheumatic diseases during the byzantine period (330-1453 a.D.) - E. Poulakou-Rebelakou; N.T. Economou; C. Tsiamis (PAGEPress Publications, 2011)
Most Byzantine medical texts described the rheumatic diseases. The Byzantine physicians, based on the ancient Greek texts, explained the causes of rheumatic diseases, described their symptoms and proposed certain treatments. The Byzantine medical sources described various types of rheumatic diseases, as inflammatory arthritis, chronic deformans polyarthritis, and gout. As it can be concluded by the available medical sources, during the Byzantine period rheumatic diseases constituted a serious medical and social problem, reprenting a remarkable cause of disability, and this complaint was part of the epidemiological interest of the Byzantine physicians.